Registration of stereo and temporal images of the retina - Ritter, N.; Owens, R.; Cooper, J.; Eikelboom, R.H.; Van Saarloos, P.P. (IEEE transactions on medical imaging, 1999)
The registration of retinal images is required to facilitate the study of the optic nerve head and the retina. The method the authors propose combines the use of mutual information as the similarity measure and simulated annealing as the search technique. It is robust toward large transformations between the images and significant changes in light intensity. By using a pyramid sampling approach combined with simulated reannealing the authors find that registration can be achieved to predetermined precision, subject to choice of interpolation and the constraint of time. The algorithm was tested on 49 pairs of stereo images and 48 pairs of temporal images with success.